Pengawasan sebagai Instrumen Peningkatan Disiplin Kerja Aparatur Sipil Negara: Studi Kualitatif pada Dinas Komunikasi, Informatika dan Statistik Kota Bima - Syahri Ramadoan; Sahrul Sahrul (Lembaga Pengembangan Kinerja Dosen, 2026)
Work discipline among civil servants is a fundamental element in achieving effective, professional, and accountable public governance. Supervision serves as a key managerial function to ensure employee compliance with organizational regulations while improving the quality of public service delivery. This study aims to analyze the implementation of the supervisory function in improving employee work discipline and to identify the obstacles encountered along with the strategies adopted to address them at the Department of Communication, Informatics, and Statistics of Bima City. A descriptive qualitative approach was employed using in-depth interviews, observation, and document analysis. Informants were selected purposively based on their involvement in supervisory activities. The findings reveal that supervisory practices have been implemented through embedded supervision, direct supervision, and administrative supervision supported by attendance monitoring, Employee Performance Target (SKP) evaluation, regular briefings, work monitoring, and hierarchical coordination. Continuous supervision contributes to improving employee compliance with working hours, task completion, and organizational responsibilities. Nevertheless, several challenges remain, including limited supervisory time, diverse employee characteristics, inconsistent corrective actions, and coordination complexity across organizational units. To address these issues, the organization strengthens embedded supervision, improves inter-unit coordination, enhances continuous coaching, optimizes organizational communication, and utilizes personnel documents as administrative control instruments. The study concludes that supervision is a dynamic managerial process that plays a strategic role in fostering employee work discipline. These findings contribute to the development of public administration literature and provide practical recommendations for strengthening internal supervisory systems within local government organizations.